(untitled) (Altre Modernità, 2016)
This essay analyses the use of crime fiction in Francisco Goldman’s reportage The Art of Political Murder, and the contribution this makes to political change in the recent history of Guatemala. The aim of Goldman’s investigative report was not just to find a murderer, but above all to criticize the abuses of power perpetrated with impunity by the ‘State’, and the practices put in place to eradicate dissidence. To understand how the features of detective fiction are used in journalism to support the search for truth, the essay examines the social power of different typologies of Crime Novel. Goldman’s The Art of Political Murder is read from the viewpoint of literary Testimonio, against the Guatemalan and Central-American literary background, to see how it can contribute to the current struggle for identity.